Behavioural and histopathologic effects following intracerebroventricular administration of tramadol in rat [Siçanlarda i̇ntraserebroventriküler tramadol uygulaniminin nörotoksik etki açisindan araştirilmasi] - (:unkn) unknown (My University, 2002)
The aim of this study was to carry out behavioural and histological examinations in rats to determine whether intracerebroventricular administration of tramadol produces spinal cord lesions. Eighteen Sprague-Dawley rats, weighing 200-300 g were implanted with an intracerebroventricular cannula after anaesthetizing with ketamine hydrochloride (100 mg/kg) and chlorpromazine (0.75 mg/kg) intraperitoneally. They were assigned into three groups, receiving either a single injection of 6 μg tramadol (n=7), two repetitive injections on consecutive days of 6 μg tramadol (n=7) or saline (n=4) in 10 μL volumes. Neurobehavioural changes were examined until the day of killing. Animals were killed 48 hours after the last injection and brain and spinal cord section slides were examined with light microscopy. Gliosis was seen in the spinal cords of three of seven rats in group I and II. Five rats in group I, six in group II, and four in group III had red neurons in cerebellum and spinal cord sections. There was no difference between the groups (p>0. 05). In conclusion, intracerebroventricular administration of tramadol in rat produced no abnormal behavioural and histopathologic results. But further studies with different doses and with the examination of the sections under electron microscopy should be done before using in humans.
Keywords: Intracerebroventricular injection; Neurotoxicity; Tramadol